2006
DOI: 10.1158/0008-5472.can-06-1280
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Phosphatase-1 Is Required for Cisplatin Resistance

Abstract: Mitogen-activated protein kinase (MAPK) phosphatase (MKP)-1 is a member of the MKP family that negatively regulates MAPK signaling. MKP-1 has been implicated in cell survival in response to stressful stimuli, including anticancer treatment, but its role in cisplatin resistance is not fully understood. Here, we show that cisplatin induces MKP-1 in several human cancer cell lines. Induction of MKP-1 by cisplatin was through the transcriptional mechanism regulated by extracellular signal-regulated kinase (ERK). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
96
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 32 publications
10
96
0
Order By: Relevance
“…MKP-1 was found to be overexpressed in a number of human cancer tissue or cell lines [87], and to contribute to the tumorigenicity of pancreatic cancer cells [88]. Recently, Wang et al have shown that MKP-1-deficient embryonic fibroblasts more readily undergo apoptosis than wild-type cells upon exposure to cisplatin [89], a chemotherapeutic drug widely used in cancer treatment. Thus, the selective inhibition of MKP-1 expression or activity may represent a valuable strategy to overcome drug resistance and improve the efficacy of cancer chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…MKP-1 was found to be overexpressed in a number of human cancer tissue or cell lines [87], and to contribute to the tumorigenicity of pancreatic cancer cells [88]. Recently, Wang et al have shown that MKP-1-deficient embryonic fibroblasts more readily undergo apoptosis than wild-type cells upon exposure to cisplatin [89], a chemotherapeutic drug widely used in cancer treatment. Thus, the selective inhibition of MKP-1 expression or activity may represent a valuable strategy to overcome drug resistance and improve the efficacy of cancer chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Negative regulation of MAP kinases, including JNK, is mediated primarily by MAP kinase phosphatases (MKPs), a group of 11 dual-specificity phosphatases that dephosphorylate the regulatory threonine and tyrosine residues. 22 MKP-1 was the first of this family to be associated with cell cycle progression (G 0 to G 1 transition) and resistance to cytotoxicity by a variety of genotoxic stresses, [23][24][25] through modulating the MAP kinase activity, 26,27 which contributes to carcinogenetic processes. 28,29 However, MKP-1 may cause cellular differentiation through inhibiting ERK, a promoter of the cell cycle and growth, resulting in strong suppression of tumor development.…”
mentioning
confidence: 99%
“…Our data argue against this possibility, as we detected similar ROSgenerating ability and expression of antioxidant enzymes in the anthracycline-sensitive and resistant AML cell lines. Aberrant expression/function of the large number of MAP3K kinases upstream to JNK (MEKK's, MLK's, DLK, ASK1/2, TAK1 and TPL2), 7 or of the downstream-negative regulators of JNK signaling (for example, MAPK-phosphatase family proteins) in resistant AML cells, 35 may also represent other mechanisms of JNK suppression in resistant AML blasts. However, it is also possible that the suppression of anthracycline-induced JNK signaling is more complex.…”
Section: Discussionmentioning
confidence: 99%